RITUEL INTERAKTION OG ILLUSION: En relationel tilgang - Houseman, Michael; Severi, Carlo (Tidsskriftet Antropologi, 2000)
By providing an explicitly formal account of three ethnographic examples – the Naven rite of the Iatmul (Papua New Guinea), Amerindian shamanism as illustrated by the Kuna (Panama), and African male initiation among the Wagania (Democratic Republic of Congo) – the authors outline a “relational” approach to the analysis of ritual action. They suggest that the illusion implied by the effectiveness of ritual action derives not from the inherent nature of the items of behaviour involved, but from the particular kind of internal consistency that is imposed by the interactive context in which they occur. Thus, the singular realities constructed through ritual performances are built up and sustained, neither by their functional or semantic properties nor by their syntactic features (for example repetition or fragmentation), nor by qualities depending on pragmatic considerations (performativity, staging procedures, etc.). Rather, they are constructed primarily by the establishment of a particular type of relational configuration.